Changes on the Physical Structure Caused by the Advanced Grinding Process before Direct Reduction of Chalcophyrite Concentrate with Carbon - Boyrazli, Mustafa; Öztürk, Elif Arancı; Slmn,; Süner, Mustafa; Çelik, Emrah; Başbağ, Güneş (My University, 2024)
After selecting the appropriate pyrometallurgical or hydrometallurgical methods according to the type of ore used in copper production, electrometallurgical refining processes are applied to reach the desired purity level. When mechanical activation processes are applied before reduction processes, they have changed the traditional workflow scheme in many processes by both shortening the process and reducing energy consumption. This study constitutes the first stage of the direct reduction of chalcopyrite in the presence of carbon and quicklime. The mixture consisting of biochar, quicklime and concentrated chalcopyrite was mixed in a stoichiometric ratio and over-ground in a spex type mill for different periods of time. Changes in the physical structure of the over-ground mixture were examined by XRD, SEM and EDX images. XRD images showed that there was a large amount of amorphization in the crystal structure as a result of excessive grinding of the material for 60 minutes. According to the DLS analysis results, it was observed that the grain size decreased to 5240 nm due to increasing grinding time.
Keywords: Advanced grinding; biocoal; chalcopyrite; direct reduction; spex